YEVROPA ITTIFOQIDA EKOLOGIK SOLIQLAR VA ULARNING IQTISODIY SAMARASI (Marketing Journal, 2026)
AbstractThe article examined the environmental taxation system and its economiceffectiveness in the European Union member states. Arthur Pigou’s theory ofexternalities and Lawrence Goulder’s double dividend hypothesis were applied as the theoretical framework. Statistical information from Eurostat and the World Bank wasused to analyse the structure of environmental tax revenues, their role in the economy,and the distribution across tax categories. The findings indicated that environmentaltaxes contributed to emission reduction without generating negative effects oneconomic development. Sweden’s carbon tax experience demonstrated that theimplementation of carbon pricing improved environmental indicators whilemaintaining stable economic growth. The study showed that the gradual introductionof environmental taxes and effective revenue recycling generated positive economicand environmental outcomes.Keywords: environmental tax, carbon pricing, double dividend, Pigouvian tax,green fiscal reform, emissions trading system.